The films of Charles & Ray Eames. - Eames, Charles; Eames, Ray; Demetrios, Eames; Peck, Gregory, 1916-2003 (Pyramid Film & Video, 2000)
Powers of ten: illustrates a picnic in Chicago and then begins moving ten times farther out every ten seconds, until our own galaxy is visible only as a speck of light. Then, we move inward into the hand of a sleeping picnicker with ten times more magnification every ten seconds.